KARAKTERISTIK PETANI MISKIN DAN PERSEPSINYA TERHADAP PROGRAM JARING PENGAMAN SOSIAL DI PROPINSI JAWA TIMUR - E.M., ROOSGANDHA; DARWIS, VALERIANA (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol. 3, No. 2 Juli 2003)
One of the economic crisis impacts was the increasing of poverty population in Indonesia, according to the BPS data in last year of 1998 the poverty in habitant was about 49,5 milions people. To minimize the growth of poverty, the government has launched Social Safety Net ( SSN ) Program. This article was to identify what characteristics that stick of the poor family and how their perception on the SSN Program. The survey was carried out on 160 respondents in two regencies in East Java. The survey result showed of the poor family members were low educational level and they were dominantly engaged in agricultural sector. In participating with the SSN program, their mostly conducted whatever the government told, because they didn’t know much about the program afterall. Eventhough there were several weaknesses, but they still enjoyed out could and hoped the program would be sustained.
Keywords: Economic Crisis, Poverty in Habitant, Social Safety Net Program, The Growth of Poverty.